The Phosphate Levels of Critically ill Patients with Respiratory Failure - Mehmet Turan İnal; Dilek Memiş; Necdet Süt (Galenos Yayinevi, 2011)
Objective: The incidence of hypophosphatemia is higher in critically ill patients and prolonged the length of ICU stay and duration of mechanical ventilation. This study evaluated the prognostic value of phosphate levels in critically ill patients. Materials and Methods: All patients admitted to the general and surgical intensive care unit (ICU) of Trakya University Medical Faculty, with respiratory failure during 1 year period (from January 1, 2009, to December 31, 2009), were retrospectively enrolled. The phosphate levels, age, gender, length of ICU stay, duration of mechanical ventilation, APACHE II scores, medical drug usage and prognosis were recorded. Hypophosphataemia was defined as a level under 2.5 mg/dL and normophosphatemia was defined as a level between 2.5-4.7 mg/dL. Results: 139 patients were retrospectively enrolled into the study, of these, 41% had hypophosphataemia. There was no statistically significant difference in age, gender and APACHE II scores. The length of ICU stay was 20.16±16.31 days in hypophosphatemic patients and 12.62±12.43 days in normophosphatemic patients (p<0.05). The duration of mechanical ventilation was 17.54±16.27 days in hypophosphatemic patients and 9.94±11.55 days in normophosphatemic patients (p<0.05). The usage of catecholamines, beta adrenergic receptor agonists, diuretics and glucocorticoids were higher in hypophosphatemic patients (p<0.05). Conclusion: The duration of mechanical ventilation and the length of ICU stay was prolonged in hypophosphatemic patients with respiratory failure. We suggested to follow the phosphate levels tightly for early diagnosis and treatment of phosphate deficiency. (Journal of the Turkish Society of Intensive Care 2011; 9: 19-22)